Atitudes frente à síndrome da imunodeficiência adquirida (SIDA) e o atendimento domiciliar do paciente - Figueiredo, Marco Antonio de Castro; Coelho, Wilson Ferreira (Brazilian Journal of Sexually Transmitted Diseases, 1996)
Using the affective-cognitive conception of altitudes proposed by Fishbein and Ajzen (1975) as a theoretical reference point, 36 mothers of patients infected or not with HIV were interviewed and 23 contents related to treatment, disease and patient were defined in order to obtain information for the planning of home care support for patients with Acquired Immunodeficiency Syndrome. Factorial Analysis by the Varimax Rotation System of 91 observations with university students, taking as criterion saturations of more than .50 for item inclusion and E. V. above 1.00 for factor composition, seven dimensions wcre isolated, related to A vers ion/Im potcncc, Form s of Contagion, Psychological Responec of the Patient, Support/Clinical Follow-up, Ambivale nce Relation/Treatment, Oppos ition/ Rcs istance to the D isease, Escape/Solitude. On the basis of these dimensions, the data obtained for mothers of individuais wiúi and without HIV infection were compared by the Mann-Whitney test, with úte levei of sig,úticance seta p <.05. Significant values for Escape/Solitude (Zu= -1.97; P= .04), suggest that the mothcrs of noninfected individuais are more prone to express the beliefs about the social isolation due to AIDS. Separate studies of the cog1útive and affective components indicated, for A version/lm poten ce, significant differences about the contents related to "faith in God" (Zu= -2.71, p= .007), suggesting the presence of a teleologic perspective among the mothers of HIV-infected patients with respect to the treatment of AIDS. Furthennore, the mothers of non-HlV-infected individuais presented sharper cognitions about lhe need for the patients to pe1fonn productive activities, soas to facilitate treatment. ln view of these results, some perspectives about the involvement in home treatment of AIDS are analyzed, cons idering some differential peculiarities of mothers of patientsHIV -infected individuais detected in the present study.